Planejamento educacional: monitoramento, avaliação e controle social do Plano Municipal de Educação de Votorantim/SP - Silva, Camila Vieira Genkawa (2023)
Through Law No. 13,005, of June 15, 2014, it was established that the Union, the States, the Federal District and the Municipalities should prepare their education plans. The objective of this research was to analyze the monitoring, periodic evaluations and ways of working of the bodies responsible for the Municipal Education Plan of Votorantim/SP, taking as a cut the period from 2015 to 2020, considering the work schedule, the monitoring flow, the assessment flow and referrals for flow correction. The research was exploratory, qualitative, bibliographical, with a semi-structured interview, taking Bardin's (2011) and Chizzotti's (2006) conceptualization as a reference, with a view to: a) discussing the National Education Plans in Brazil and the process evaluation and monitoring of its implementation among guidelines and technical guidelines; b) establish relations between the Municipal Education Plan of Votorantim and the call for evaluation and monitoring, regarding the design and scope of the foreseen goals; c) explain the perceptions of respondents in the municipality, through a semi-structured interview (member of the Coordinating Commission and Technical Team for monitoring and evaluation and form for members of the Municipal Council of Education), with a view to highlighting the referrals made in the context of social control in the implementation process. Considering that monitoring and evaluation provide subsidies for adjustments and improvements, while social control increases the transparency and responsibility of educational actions, the interviews with respondents showed the paths taken, but denoted impasses experienced as in technical training, mentioning that the carried out was not enough for the participants to understand the “step by step” of monitoring. Respondents also reported the need for dialogue with other municipalities, a lot of study on the subject, and it was reported that there was no support from the federal government to resolve doubts. Therefore, the results of the research indicated that the monitoring process, periodic evaluations and ways of working of the bodies responsible for the Municipal Education Plan of Votorantim/SP, in the period from 2015 to 2020, occurred, but it was evidenced in the speech of the respondents the limits and weaknesses regarding the principles of participation and social control, which lack constant qualifications, especially the coordination of actions, with the objective of fulfilling the established goals.